2022
DOI: 10.1097/mph.0000000000002551
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher Disease Type 2 Manifested as Hemophagocytic Lymphohistiocytosis in a Neonate in the COVID-19 Era

Abstract: Background: A term neonate presented with persistent severe thrombocytopenia, elevated liver enzymes, conjugated hyperbilirubinemia, hepatosplenomegaly, and mild hypotonia.Observations: A thorough workup for infections, congenital thrombocytopenias, and neonatal malignancies was negative. Because of increased anti-SARS-CoV-2 IgG antibodies after maternal COVID-19, multisystem inflammatory syndrome of neonates was considered and intravenous immunoglobulin was administered. The clinical condition of the neonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Studies were excluded if they did not discuss nHLH ( n = 280); aggregated nHLH patient data with all ages ( n = 83); provided insufficient detail and/or data describing a case of nHLH ( n = 28); and for other reasons ( n = 8). Two‐hundred‐five cases of nHLH from 142 articles were included in our analysis 12–152 …”
Section: Resultsmentioning
confidence: 99%
“…Studies were excluded if they did not discuss nHLH ( n = 280); aggregated nHLH patient data with all ages ( n = 83); provided insufficient detail and/or data describing a case of nHLH ( n = 28); and for other reasons ( n = 8). Two‐hundred‐five cases of nHLH from 142 articles were included in our analysis 12–152 …”
Section: Resultsmentioning
confidence: 99%
“…The detailed characteristics of the included studies are shown in Additional file 2 : Table S3. There were 73 case report [ 4 6 , 8 , 9 , 25 32 , 37 39 , 44 , 45 , 49 , 51 , 53 60 , 67 69 , 72 , 76 79 , 82 84 , 86 88 , 90 , 91 , 93 , 94 , 96 , 99 107 , 109 114 , 116 , 119 123 , 126 , 127 , 129 – 131 ], 38 cohort [ 7 , 10 , 19 , 33 – 36 , 40 43 , 46 48 , 50 , 52 , 61 66 , 70 , 71 , 73 , 74 , 80 , 81 , 92 , 95 , 97 , 98 , 108 , 117 , 118 , 124 , 125 , 132 ], 4...…”
Section: Resultsmentioning
confidence: 99%
“…Only six studies were made within multi-countries (n = 6) [ 10 , 33 , 35 , 51 , 95 , 132 ]. The majority of the studies were single centre [ 4 6 , 8 , 9 , 19 , 25 32 , 34 , 37 39 , 41 , 43 47 , 49 , 50 , 52 60 , 62 , 64 , 66 69 , 71 , 72 , 75 80 , 82 84 , 86 90 , 93 , 94 , 96 , 98 – 117 , 119 131 ] and only 23 studies were multi-centre [ 7 , 10 , 33 , 35 , 36 , 40 , 42 , 48 , 51 , 61 , 63 , 65 , 70 , 73 , 74 , 81 , 85 , 91 , 92 , 95 , 97 , 118 , 132 ]. Among all included studies in our systematic review, only one study reported on the other potential modifiers in immunity-related pathways for all diagnosed IEIs in children who were infected with SARS-CoV-2 (n = 1, 0.9%) […”
Section: Resultsmentioning
confidence: 99%
“…Patients with GD type II, in particular, have severe hepatosplenomegaly and cytopenia from birth. Most cases of HLH associated with GD have neonatal onset, [89][90][91] and even if therapeutic intervention for HLH is performed, the prognosis is poor. Glycosylceramide, a GD metabolite, is found in macrophages, reticuloendothelial cells, monocytes, T cells, B cells, and dendritic cells.…”
Section: Other Iemsmentioning
confidence: 99%
“…Other IEMs associated with HLH have been reported (Table 5). 81–103 Propionic acidemia (PA) and Gaucher disease (GD) are relatively common causes of HLH. Two cases of PA and one case of methylmalonic aciduria (MMA) with HLH were reported by Gokce, et al 81 Three patients received immunochemotherapy, but the patient with MMA died as a result of multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%